Kesiapan Sekolah Menengah Atas dalam Implementasi Kurikulum Tingkat Satuan Pendidikan di Kota - Mustofa, - (Jurnal Ekonomi dan Pendidikan, 2012)
A number of schools in Yogyakarta have been trying to implement the KTSP. However, schools still struggle to understand the curriculum. The government has stated that schools which are ready can implement the KTSP by 2007, and those which are not can postpone the implementation until the end of 2009/2010. A study of the schools’ readiness to implement the KTSP was conducted at four schools in Yogyakarta. The research aims at (1) describing the schools’ readiness to implement the KTSP; (2) identifying the needs of the school to implement the KTSP; (3) finding out the supporting and inhibiting factors of the KTSP implementation. The readiness to implement the KTSP varied from one school to another. The varieties include several aspects, such as: curriculum properties, facilities, finance, environment, principal’s leadership, teachers and staffs’ readiness, and parents and students’ readiness. It was also revealed that what were needed by the schools to implement the KTSP were commitment and financial support from the government and teachers’ understanding of the curriculum through training. The inhibiting factor was inconsistent policy.